2020
DOI: 10.1093/ejcts/ezaa068
|View full text |Cite
|
Sign up to set email alerts
|

Pacemaker implantation after aortic valve replacement: rapid-deployment Intuity® compared to conventional bioprostheses

Abstract: OBJECTIVES The aim of this study was to compare the incidence of permanent pacemaker (PPM) implantation after aortic valve replacement by rapid-deployment bioprosthesis (RDB) and standard valve (Standard). METHODS All patients undergoing aortic valve replacement between 2015 and 2018, in 1 centre, were included. A multivariate analysis on the whole cohort and then a propensity score matching were used to compare the 2 groups.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(25 citation statements)
references
References 27 publications
3
22
0
Order By: Relevance
“…We found that sinus rhythm (SR) decreased in frequency over time (P <.001) and left bundle branch block (LBBB) increased in frequency over time (P ¼ .006). A study by Herry and colleagues 6 had similar findings from a single-center experience where they compared EIV with conventional aortic valve bioprosthesis. No significant changes in the frequencies of atrial fibrillation, first-degree heart block (HB), and right bundle branch block (RBBB) were noted over time.…”
Section: Discussion Electrocardiogram Changes After Rapid Deployment Of Aortic Valve Replacementmentioning
confidence: 69%
“…We found that sinus rhythm (SR) decreased in frequency over time (P <.001) and left bundle branch block (LBBB) increased in frequency over time (P ¼ .006). A study by Herry and colleagues 6 had similar findings from a single-center experience where they compared EIV with conventional aortic valve bioprosthesis. No significant changes in the frequencies of atrial fibrillation, first-degree heart block (HB), and right bundle branch block (RBBB) were noted over time.…”
Section: Discussion Electrocardiogram Changes After Rapid Deployment Of Aortic Valve Replacementmentioning
confidence: 69%
“…In our prespecified subgroup analysis, SuAVR did not significantly reduce mortality in high risk patients (OR: 0.16, 95% CI [0.02, 1.35], p = .09, Twenty studies (n = 26,812, SuAVR = 8635, SAVR = 18,177) reported stroke. [19][20][21][22][24][25][26]28,[41][42][43]46,67,[69][70][71][72][73][74][75] Stroke was similar between SuAVR and SAVR (OR: 1.04, 95% CI [0.82, 1.32], p = .77, I 2 = 6%, very-low quality). We did not detect publication bias on visual inspection.…”
Section: Search Resultsmentioning
confidence: 95%
“…49,53,54,62 Overall, 45 studies were at high risk, 34 studies were at unclear risk, and no studies were at low risk of bias. Appendix 2 includes risk of bias assessment of We pooled results from 26 studies [19][20][21][22][24][25][26][28][29][30][41][42][43][44]60,[65][66][67][68][69][70][71][72][73][74][75] (n = 27,614; SuAVR = 9028, SAVR = 18,586). The 30-day and 2-year mortality were similar between the two groups (30-day, OR: 0.99, 95% CI [0.85,1.16], p = .93, I 2 = 0%, very-low quality) and (2-year, OR: 0.99, 95% CI [0.43,2.30], p = .98, I 2 = 7%, very-low quality).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations